Classic cocktails from around the world - Gage, Allan (London, United Kingdom : Hamlyn Publishing Group Limited, 2006)
A guide to the best cocktails and the bars that made them great - the world's hottest, and coolest, places to be seen. It includes delicious recipes that feature alongside their creators, the movers and shakers who drank them, and the bars they are synonymous with, each one captured by historical and contemporary photography.
Introduction -- Europe -- Africa -- Asia -- Australasia -- South+Central America -- Carribean -- North America
Includes index.
Keywords: COCKTAILS